Why should government intervene in a market economy? : a Caribbean perspective on the hospitality and tourism sector - Mc David, Hilton ([s.n.] [S.l.], 2002)
Explores the rationale for the involvement of government in the hospitality and tourism sector, and alternatively the circumstances under which it can be justified. Discusses the established and potential roles of the government in the sustainable development of the sector along with the politics of tourism.